Edukasi pentingnya pendidikan bagi generasi muda untuk menghindari putus sekolah dan pernikahan dini - Safitri, Dhanny; Hasany, Tifani Dame; Asri, Ni Wayan Adelia Mutiara; Ibrahim, Isra Dewi Kuntary; Muhtarom, Zamroni Alpian (Nur Science Institute, 2025)
There are various social problems faced by the young generation in Montong Ajan Village, Central Lombok Regency, West Nusa Tenggara Province. Two of the most serious issues are the high number of early marriages and the low number of people who receive higher education due to dropping out of elementary or junior high school, or senior high school. Based on this, this community service activity aims to increase insight and understanding of the importance of education for the young generation, especially students of SMP Islam Tanwirul Qulub Sengketan in Montong Ajan Village. This activity is carried out using a counseling approach that includes lectures, interactive discussions, educational games, evaluations, and the distribution of stationery. It is hoped that through this series of activities, students will become more motivated to stay in school, discover their interests, and explore job options available to them, as well as delay marriage to achieve a better quality of life. Overall, it can be concluded that community service activities can be carried out effectively and receive positive responses from the participants. In the future, similar activities should be carried out in other schools in Montong Ajan Village or in areas experiencing similar social problems to provide more significant and broader benefits for the younger generation.